IMPLEMENTASI JUS BUAH PARE PADA PERAWATAN PASIEN DIABETES MELLITUS DENGAN MASALAH KETIDAKSTABILAN KADAR GULA DARAH DI RUANG KENARI ATAS RSUD AJIBARANG - Saino Saino; Siti Robi’ah Yuniatun; Amin Susanto (Jurnal Inovasi Penelitian, 2022)
Diabetes mellitus (DM) is a chronic disease that causes high rates of morbidity and mortality. Hyperglycemia is a typical symptom of Type II DM which causes disturbances in blood glucose levels. The key to treating DM is to control the amount of blood sugar. Pare is used for treatment, especially for the treatment of diabetes mellitus because it contains saponins which have the effect of lowering blood sugar levels. Descriptive research design in the form of a case study with a nursing process approach consisting of assessment, nursing diagnoses, planning, implementation, and evaluation by focusing on nursing implementation in patients with diabetes mellitus with risk problems of blood glucose level instability by giving bitter gourd juice. The subject of the case study amounted to one case, namely a patient with diabetes mellitus in the Upper Kenari Room, Ajibarang Hospital. The results showed that the problems that occurred in the client could be resolved on the 3rd day and were marked by the patient looking more relaxed, no longer sweating cold, BP: 141/90 mmHg, N: 82 x/min, S: 36.7 °c , RR : 22 x/min, Spo2 : 95%, GDS : 280 mg/dL, the patient says that he is not dizzy, his weakness has decreased, he has eaten and drank a lot.